Norvegų kalbos gramatika / Norwegian Grammar - Mickūnaitė Griškevičienė, Aurelija (Scandinavistica Vilnensis, 2018)
The publication is a revised and expanded edition of Norwegian Grammar published in 2012. It is aimed at Lithuanian students of Norwegian. It describes Norwegian word classes and the sentence structure and pronunciation in detail, and provides explanations of a number of linguistic features that are not characteristic of the Lithuanian language. The book contains quite a few examples of language usage and illustrations of grammatical constructions that are all translated into Lithuanian.Ši knyga – papildytas ir atnaujintas 2012 m. išleistos „Norvegų kalbos gramatikos“ leidimas. Tai praktinė gramatika, skirta besimokantiems norvegų kalbos. Joje išsamiai aprašomos norvegų kalbos dalys, sakinio struktūra, tarimas, paaiškinama nemažai kalbos reiškinių, kurie nebūdingi lietuvių kalbai. Knygoje gausu kalbos vartosenos pavyzdžių, gramatinių konstrukcijų iliustracijų. Kad skaitytojui būtų lengviau suprasti, visi pavyzdžiai išversti į lietuvių kalbą.
Keywords: Norwegian grammar; Learner’s grammar